Digital Islamic Finance Research Trends: A Bibliometric Analysis of Legal Transformation and Social Practices in the Global Islamic Financial System - Muhammad Distian Andi Hermawan (Contemporary Islamic Law and Legal Issue, 2026)
The objectives of this study are as follows: To analyze the global trend of publications on digital Islamic finance in the last seven years using a bibliometric approach. Identify the main themes, author collaboration patterns, core journals, and dominant countries in Islamic finance digital research. Uncovering research gaps related to legal and social aspects in Islamic finance digitalization. Explain how digital transformation affects legal structures, fatwa practices, and social behavior in the Islamic financial ecosystem, developing future research directions based on bibliometric findings.  This study uses a mixed-method approach based on Bibliometric analysis and Systematic Literature Review (SLR). This approach was chosen because it is able to provide a comprehensive overview of research developments, intellectual mapping, and research gap identification in the field of digital Islamic finance. Bibliometric results show that the trend of digital Islamic finance research shows that this topic is experiencing rapid development and is increasingly gaining global attention in the period 2018–2024. The growth of publications increased significantly, especially after 2021, indicating the increasing urgency of digitalization in the Islamic financial system. The emergence of themes such as blockchain, artificial intelligence, central bank digital currency (CBDC), and Islamic fintech shows that digital transformation is not only technological, but also closely related to regulatory issues, governance, and social implications. From the author's and institutional side, it can be seen that there is a concentration of contributions from several researchers and certain study centers, reflecting the formation of an active scientific community..